2008
DOI: 10.1002/ppul.20783
|View full text |Cite|
|
Sign up to set email alerts
|

Establishment of a web‐based registry for rare (orphan) pediatric lung diseases in the United Kingdom: The BPOLD registry

Abstract: We have demonstrated the successful establishment of a low cost, web-based registry for children with rare lung diseases. There is an urgent need for European and International collaboration with the establishment of electronic registries for children with rare diseases, if the inequities of health care are to be addressed. A web-based approach, similar to the one we have developed, will enable this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 15 publications
1
36
0
1
Order By: Relevance
“…This gap is increasingly addressed by clinicians through the establishment of research networks and registries, including the British Paediatric Orphan Lung Disease registry,44 the UK Obstetric Surveillance System,45 and the InterRett database 46. The Rare Diseases Clinical Research Network35 and Orphanet34 facilitate the development of registries, national centres of reference and research networks.…”
Section: Resultsmentioning
confidence: 99%
“…This gap is increasingly addressed by clinicians through the establishment of research networks and registries, including the British Paediatric Orphan Lung Disease registry,44 the UK Obstetric Surveillance System,45 and the InterRett database 46. The Rare Diseases Clinical Research Network35 and Orphanet34 facilitate the development of registries, national centres of reference and research networks.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, patient registries, such as the British Pediatric Orphan Lung Disease Registry (www.bpold.-co.uk), afford an opportunity to increase our understanding of these rare diseases by accumulating a data set on children with cystic lung lesions. 38 …”
Section: Introductionmentioning
confidence: 99%
“…Although several specialty epidemiological surveillance systems have adopted electronic card reporting,8 this is the first system we are aware of that has been used by a specific group of physicians to actively and regularly report ADRs 3. Clarkson et al have shown paediatricians are willing to report but this has never been activated on a national scale 4.…”
Section: Discussionmentioning
confidence: 99%